Pengembangan Buku Saku Perwasitan Tenis Meja Berbasis Flipbook - Al Ilham; Joni Taufik Hidayat; Muhammad Faisal Lutfi Amri; Juni Isnanto; Arief Ibnu Haryanto (Journal on Education, 2023)
The purpose of this research is to produce a table tennis refereeing pocket book that specifically discusses table tennis game rules, the functions and duties of the umpire and violations committed by players and coaches in table tennis games based on flipbooks as a guide and guide for the umpire in leading a match. The method used in this study is the ADDIE development model. The sample at the implementation stage consisted of 10 referees who did not have a license and 30 people consisting of referees, players and coaches, including 3 national referees and several national players and coaches. The data collection techniques are interviews, validation and questionnaires. Quantitative descriptive analysis techniques are used to process data in the form of numbers (scores) obtained through questionnaires. The results of the research at the implementation stage were carried out on a small-scale trial of 3.39 and a large-scale trial of 3.51 with a very feasible category. Flipbook-based table tennis refereeing pocket books are included in the very appropriate category, this is based on the assessment of 3 material experts with an average value of 3.73 and 1 media expert with a value of 3.41. Therefore the table tennis refereeing pocket book is very appropriate to use, practical and interesting as a guide for referees in increasing knowledge of table tennis game rules.